Electrical conductivity of Ag-Na ion exchanged soda-lime glass - Braunger, Maria L. [UNESP]; Escanhoela, Carlos A.; Ziemath, Ervino C. [UNESP] (Elsevier B.V., 2014)
This paper reports on a study of the influence of silver on the electrical conductivity of Ag-Na ion exchanged soda-lime-silica glass. A glass of 22Na(2)O.8CaO.70SiO(2) (mol %) composition was prepared and silver was introduced into its samples by Ag-Na ion exchange at 350 degrees C for 1 h. The ion exchanged samples were further subjected to a thermal treatment at 500 degrees C for 24 h. Complex impedance diagrams (-Z '' vs. Z' plots) at several temperatures were obtained to calculate the activation energy for the dc electrical conductivity, Ea. The electrical conductivity of the ion exchanged sample is close to that of the pristine sample. The complex impedance plots of this sample show a tail in the low frequency range assigned to the non-uniform distribution of silver in the surface layers and stresses produced by the thermal and chemical temperings. The electrical conductivity of the layers was lower than that of the pristine glass. The further thermal treatment reduced the conductivity of the sample due to the formation of metallic silver nanopartides in the glass matrix and the lower concentration of the mobile Na+ ions. UV-visible optical absorption spectra showed an absorption band at 420 nm attributed to the presence of silver nanoparticles in the thermally treated sample. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Impedance spectroscopy; Silicate glasses; Ag-Na ion exchange; Silver nanoparticles